Sacred Plunder : Venice and the Aftermath of the Fourth Crusade - Perry, David M., 1973- (Book collections on Project MUSE., 2015)
"Explores the emergence of a body of texts about relics transported from Constantinople to the West as a after the Fourth Crusade, and the role of these texts in the development of Venice's civic identity in the thirteenth century"--